2013
DOI: 10.1038/nm.3258
|View full text |Cite
|
Sign up to set email alerts
|

Local proliferation dominates lesional macrophage accumulation in atherosclerosis

Abstract: During the inflammatory response that drives atherogenesis, macrophages accumulate progressively in the expanding arterial wall1,2. The observation that circulating monocytes give rise to lesional macrophages3–9 has reinforced the concept that monocyte infiltration dictates macrophage build-up. Recent work indicates, however, that macrophages do not depend on monocytes in some inflammatory contexts10. We therefore revisited the mechanism of macrophage accumulation in atherosclerosis. We show that murine athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

43
804
4
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(876 citation statements)
references
References 39 publications
43
804
4
6
Order By: Relevance
“…5 Myeloid cells that phagocytose lipids and form foam cells accumulate in the atherosclerotic lesion due to both monocyte immigration and local proliferation. 13 During atherogenesis, CD11c expression on aortic CD11b + myeloid cells increases. 14,15 This cell type is capable of both lipid phagocytosis and antigen presentation [14][15][16][17] and can productively interact with T cells in the murine aorta.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Myeloid cells that phagocytose lipids and form foam cells accumulate in the atherosclerotic lesion due to both monocyte immigration and local proliferation. 13 During atherogenesis, CD11c expression on aortic CD11b + myeloid cells increases. 14,15 This cell type is capable of both lipid phagocytosis and antigen presentation [14][15][16][17] and can productively interact with T cells in the murine aorta.…”
mentioning
confidence: 99%
“…5 Aortic myeloid cells mostly derive from peripheral blood monocytes at early stages of atherosclerosis development. 13 Multiple chemokines have been implicated in this, including fractalkine receptor CX3CR1, which promotes lesion progression. 10,19 CX3CR1 is expressed on leukocytes, including monocytes, dendritic cells, T cells, and natural killer cells, 20 but also nonmyeloid cells such as aortic smooth muscle cells.…”
mentioning
confidence: 99%
“…Recently, it was shown that in AS more local proliferation of bone marrow derived MΦ instead of infiltration by blood monocytes occurs [43,44]. As shown in mice, the infiltrations rates of monocytes into plaques are additionally subset specific, whereas Ly6-C low monocytes are less recruited than their Ly6C high counterparts [43].…”
Section: The Biology Of Monocytes and Macrophagesmentioning
confidence: 96%
“…Monocyte adhesion depends on the upregulation of a number of cell-adhesion molecules on the luminal surface of the endothelium, 110 notably, ICAM1, Pselectin, and VCAM1; followed by the expression of three major chemokine families, CCR2, CCR5, and CX3C chemokine receptor 1 (CX3CR1), that facilitate the transmigration process 111,112 . After recruited from the spleen and bone marrow 113 , monocytes can terminally differentiate into macrophages 114 , differentiate and locally proliferate into distinct functional phenotypes 115 , or directly influence the phenotype of in situ cells (for example, lesional macrophages) 116 . Lipids from retained apoB-containing lipoproteins are taken up by activated macrophages by a number of processes, including phagocytosis of aggregated LDL 117 , pinocytosis of LDL 118 , uptake of modified apoB-lipoproteins by scavenger receptors, and uptake by CD36.…”
Section: Atherosclerosis Pathogenesismentioning
confidence: 99%